Memory as a background for recovering the MISAK identity - Ortega-García, Carlos Andrés; García-Novoa, Viviana (Prospectiva. Revista de Trabajo Social e Intervención Social, 2024)
The article opens the dialogue about the dynamics of cultural resistance applied in the school San Pedro Peña del Corazón, vereda San Pedro, resguardo of Guambía, Department of Cauca. The MISAK belongs to a Colombian indigenous population, who, despite the constitutional protection of their identity, in their daily life face the transformation of their culture, a process evidenced through a participant observation exercise carried out in 2015. The recognition of their ancestral background has become a challenge for the community, and the school is proposed as an alternative that unifies tradition with academic training; in this way, new generations are offered the opportunity to be educated from their history, and to build from this, dynamics of conservation of their culture, a factor required to articulate this knowledge with what interculturality implies in the XXI century for the Colombian indigenous populations.